Work-related ability as source of information advantages of training employers - Jens Mohrenweiser; Gaby Wydra-Sommaggio; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper addresses the puzzle how employers that invest in general human capital can gain an information advantage with respect to the ability of their employees when training is certified by credible external institutions. We apply an established model from the employer-learning literature and distinguish between two ability dimensions: cognitive and work-related ability. We apply this model to the German apprenticeship system and show that cognitive ability certified by external institutions at that the end of apprenticeship training can be signalled to outside employers. Apprenticeship graduates however cannot signal their work-related ability - measured by a small voluntary bonus paid by the training employer - to the outside market. We therefore show that the information advantage on work-related ability explains that training employers can positively select the apprentices they retain. As a consequence, this information advantage induces employers to invest in certified and transferable human capital.
urn:nbn:de:bsz:180-madoc-397027
Keywords: J24; J31; J62; J63; M52; M53; 330; training; employer learning; employer change; adverse selection; asymmetric information